Outcomes of bleb revision with ologen following filtering glaucoma surgery. Issue 4 (July 2022) - Kornmann, Helen L.; Fellman, Ronald L.; Smith, Oluwatosin U.; Godfrey, David G.; Butler, Michelle R.; Grover, Davinder S.
Purpose: This study reports long-term outcomes of bleb revision with ologen™ Collagen Matrix (Aeon Astron Europe BV, the Netherlands) for the surgical management of various bleb-related issues including persistent bleb leaks with or without associated hypotony, bleb dysesthesia, overhanging blebs, or hypotony after filtering glaucoma surgery. Materials and methods: A retrospective chart review was performed for patients who underwent ologen bleb revision from 2012 to 2019 at Glaucoma Associates of Texas. Results: The study included 23 eyes of 22 patients undergoing bleb revision with the ologen implant. Mean age was 74.0 ± 11.3 years, 16 (69.6%) were female, and 13 (56.5%) were White. Indications for bleb revision included bleb leak (78.3%), dysesthesia (13.0%), and hypotony from an overfiltering bleb (8.7%). Mean preoperative intraocular pressure was 6.8 ± 4.1 mmHg and the number of medications was 0.3 ± 0.9. Median follow-up was 24 months (range: 12–84 months); all patients had at least 12 months of follow-up. At 1 year, mean intraocular pressure was 10.9 ± 4.6 mmHg on 0.2 ± 0.5 medications, and at last follow-up, mean intraocular pressure was 10.4 ± 3.6 mmHg on 0.3 ± 0.7 medications. Bleb morphology remained low, diffuse, and posterior. One patient developed kissing choroidal effusions requiring surgical drainage with subsequent stabilization of intraocular pressure and bleb function, and three patients required additional surgery due to persistent leaks or bleb failure; there were no other vision-threatening complications. Conclusions: Use of the ologen implant during surgical bleb revision is a useful surgical technique that confers long-term improvements in bleb morphology and stability of function.